Pengaruh Reward Sebagai Upaya Meningkatkan Motivasi Belajar Siswa Dalam Pembelajaran Biologi - Siska Arimadona (E-Tech : Jurnal Ilmiah Teknologi Pendidikan, 2018)
The purpose of this research is to improve students' motivation in learning biology through the reward system in class VIII.2 MTsN Koto Nan Gadang first semester of academic year 2015/2016. From the research it can be concluded that the reward system can improve students' motivation in the subject of Biology. From this research suggested the reward system should be reapplied by the teacher in tune with the students.